2016
DOI: 10.3390/w8080326
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Subsurface Agricultural Drainage on Soil Water Storage and Flows of a Small Watershed

Abstract: 3D hydrological modeling was performed, using CATHY (acronym for CATchment HYdrology model), with the basic objective of checking whether the model could reproduce the effects of subsurface agricultural drainage on stream flows and soil water storage. The model was also used to further our understanding of the impact of soil hydrodynamic properties on watershed hydrology. Flows simulated by CATHY were consistent with traditional subsurface drainage approaches and, for wet years, flows at the outlet of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…To the best of our knowledge, sediment dynamics in an agricultural drained catchment has never been measured with a high frequency. Indeed, because it has been shown that sediment transfers in headwater catchments occur during very short time periods (Meybeck et al, 2003), high temporal resolution monitoring (<1 h) is required to capture the temporal variations of these sediment fluxes, as it was previously done for water fluxes in drained cultivated environments (King et al, 2014; Muma et al, 2016). As these previous studies demonstrated the increased connectivity associated with tile drainage networks for water transfers, a similar investigation should be conducted on sediment transfers.…”
mentioning
confidence: 99%
“…To the best of our knowledge, sediment dynamics in an agricultural drained catchment has never been measured with a high frequency. Indeed, because it has been shown that sediment transfers in headwater catchments occur during very short time periods (Meybeck et al, 2003), high temporal resolution monitoring (<1 h) is required to capture the temporal variations of these sediment fluxes, as it was previously done for water fluxes in drained cultivated environments (King et al, 2014; Muma et al, 2016). As these previous studies demonstrated the increased connectivity associated with tile drainage networks for water transfers, a similar investigation should be conducted on sediment transfers.…”
mentioning
confidence: 99%
“…Muma et al [12] modeled a coupled surface-subsurface flow process on an agricultural watershed. They applied a physics-based 3D hydrologic model CATHY (acronym for CATchment Hydrology) at Bras d'Henri River Watershed in Canada.…”
Section: Advancing Process-based Models In Watershed Hydrologymentioning
confidence: 99%
“…Intensive studies have developed numerous IHMs to assess interactions between surface water and groundwater systems. These widely used models include the SWATMOD model [4], parallel groundwater flow (PARFLOW) model [5], MODHMS model [6], 3D fully coupled groundwater-surface model (an acronym for catchment hydrology model, CATHY) [7], HydroGeoSphere model [8], WetSpass-MODFLOW [9], J2000-MODFLOW model [10], GSFLOW model [11], and MIKE SHE [12]. The SWATMOD model couples the soil water assessment tool (SWAT) model [13] with the three-dimensional groundwater simulation (MODFLOW) model [14].…”
Section: Introductionmentioning
confidence: 99%